Factors influencing the non-compliance of halal standard among restaurant operators in Kuala Lumpur - Ab Rahman, Ilyia Nur; Ab Rahman, Suhaimi; Mat Hashim, Dzulkifly; Che Man, Yaakob (Halal Products Research Institute, Universiti Putra Malaysia, 2009)
The food service industry is deemed to be the final link in the entire food industry supply chain. Thus, it has a crucial role to ensure that the food served is safe and suitable for consumption. In Islam, looking for Halal and Toyyib food is mandatory for every Muslim. The Muslims not only need to observe that the food consumed is Halal but also safe and free from contamination. Today, as the business of Halal food experiences a rapid growth, the duty of ensuring the food is Halal has been shifted to restaurant operators and this can be seen through the introduction of Halal certification. However, many restaurant operators did not comply with this Halal standard and led to Halal fraudulent practices. Reports on Halal fraudulent decrease lack of confidence amongst the Muslims. This study attempt to identify the factors, studies the extent of the factors influencing the non compliance of Halal standard among the restaurant operators and developing the profiles of the non- compliance of Halal standard restaurant operators with various types of restaurants. The methodology used in the study involves in depth interview as well as survey. Sample of 100 restaurant operators who purported to sell food to Muslim consumer will be interviewed via structured questionnaires and series of depth interview between various enforcement bodies will be conducted. The data will be analyzed using Statistical package for Social Science version 17.0 and the Nvivo data analysis. The result will be the suggestion for further improvement on compliance towards Halal standard among restaurant operators.